Antibody Affinity Maturation in Fishes—Our Current Understanding - Brad G. Magor (Biology, 2015)
It has long been believed that fish lack antibody affinity maturation, in part because they were thought to lack germinal centers. Recent research done on sharks and bony fishes indicates that these early vertebrates are able to affinity mature their antibodies. This article reviews the functionality of the fish homologue of the immunoglobulin (Ig) mutator enzyme activation-induced cytidine deaminase (AID). We also consider the protein and molecular evidence for Ig somatic hypermutation and antibody affinity maturation. In the context of recent evidence for a putative proto-germinal center in fishes we propose some possible reasons that observed affinity maturation in fishes often seems lacking and propose future work that might shed further light on this process in fishes.